Global Inequality and the Global Inequality Extraction Ratio : The Story of the Past Two Centuries - Milanovic, Branko (2012)
Using social tables, the author makes an estimate of global inequality (inequality among world citizens) in the early 19th century. The analysis shows that the level and composition of global inequality have changed over the past two centuries. The level has increased, reaching a high plateau around the 1950s, and the main determinants of global inequality have become differences in mean country incomes rather than inequalities within nations. The inequality extraction ratio (the percentage of total inequality that was extracted by global elites) has remained surprisingly stable, at around 70 percent of the maximum global Gini, during the past 100 years.